2008
DOI: 10.1097/tp.0b013e31818a6805
|View full text |Cite
|
Sign up to set email alerts
|

Blood Group ABO Antigen Expression in Human Embryonic Stem Cells and in Differentiated Hepatocyte- and Cardiomyocyte-Like Cells

Abstract: Since clinical stem-cell therapy is likely to be performed with immature progenitor cells, blood group ABO compatibility of donor cells/recipients should be favorable to avoid unnecessary rejection problems caused by ABO incompatibility. The in vitro loss of B antigens in a genotype B hESC line indicates that loss of ABH antigens occurs early during human embryogenesis since these antigens are lacking in adult cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…The hESC lines were derived and characterized as previously described (11, 12). The hiPSC lines ChiPSC-7, ChiPSC-9, and P11012 were Cellectis in house human induced pluripotent stem cells derived by the retroviral transduction technique, whereas the derivation of ChiPSC-4 was done as described (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hESC lines were derived and characterized as previously described (11, 12). The hiPSC lines ChiPSC-7, ChiPSC-9, and P11012 were Cellectis in house human induced pluripotent stem cells derived by the retroviral transduction technique, whereas the derivation of ChiPSC-4 was done as described (13).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical analyses were performed as described (12). The hiPSC lines (ChiPSC-4, ChiPSC-7, and ChiPSC-9), and four of the hESC lines (SA002, SA121, SA181, and AS038) were cultured under feeder-free conditions, whereas the remaining three hESC lines (SA001, SA348, and SA461) were cultured on mitomycin-C-inactivated mouse embryoid fibroblast feeder layers.…”
Section: Methodsmentioning
confidence: 99%
“…(22,23) It is also reported that BG-H2 is expressed in early stage hematopoietic cells and embryonic stem cells. (24) However, the expression of BG-H2 in CSCs, particularly in colon cancer CSCs, is unknown. In this study we found that BG-H2 antigen was overexpressed on the surface of colon CSCs (CD133þ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All three are expected to be found in cell populations used to create cardiac grafts. A or B blood group antigens are expressed on ESC and ESC-derived cells [53]. These antigens are critical for safe blood transfusions.…”
Section: Antigens Classes For Stem Cell-derived Cardiomyocytesmentioning
confidence: 99%